Examination of the Transformational Leadership Practices of the Unit Charge Nurses - Emel Arslan; Fahriye Vatan (Dokuz Eylul University, 2020)
Background: The studies have revealed that the transformational leadership of nurse managers has positive impacts on patient care outcomes, nurses' organizational behavior and institutional outcomes. Therefore, it is important to evaluate the transformational leadership practices of nurse managers in health care institutions. Objective: The aim of this study is to examine the transformational leadership practices of unit charge nurses working in an training and research hospital. Method: The sample of the study, which is descriptive, consists of 218 service nurses, 17 unit charge nurses and five nurse managers working in a Pediatric Diseases and Surgery Training and Research Hospital who volunteered to participate in the research. As data collection tools, "Introductory Information Form" and "Leadership Practices Inventory (LPI)" were used. LPI consists of two forms namely "Self Evaluation" and "Observer Evaluation". In the study, unit charge nurses were evaluated by their subordinates, superiors and peers, using the "Observer Form". With the "Self Evaluation Form", unit charge nurses evaluated themselves. The unit charge nurses was evaluated by a service nurse as a subordinate, by another unit charge nurse as a peer and by the nursing services manager and supervisor nurses working in the nursing services management of the hospital, as superiors. In the analysis of the data, mean, standard deviation, percentage, variance analysis were used. Findings: According to the subordinate, peer and superior evaluations of the unit charge nurses, the means of the total score of LPI was found to be at medium level, while the sub-dimension namely ''Support on the Development of Personnel'' was higher than the other sub-dimensions. When the means of LPI of the unit charge nurses were examined according to the groups evaluating; it was determined that the scores of the superiors were highest which was followed by the scores of self-evaluation, peers and subordinates respectively. Conclusion: It has been concluded that the transformational leadership practices of the unit charge nurses are at medium level and they need to improve their transformational leadership skills, and it is suggested that on-the-job training programs and continuous training related to leadership should be supported.